2021
DOI: 10.1038/s41598-021-95659-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum PS150 promotes non-rapid eye movement sleep in the first night effect of mice

Abstract: The first night effect (FNE) is a type of sleep disturbance caused by an unfamiliar environment, which leads to difficulty falling asleep and reduced sleep duration. Previously, we reported that Lactobacillus fermentum PS150 (PS150) improves sleep conditions in a pentobarbital-induced sleep mouse model. In this study, we aimed to evaluate the effect of PS150 on the FNE in mice. Briefly, mice were implanted with electrodes and orally administered PS150 for four weeks, and then the FNE was induced by cage changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Two studies have shown the sleep-promoting effects of a single Lactobacillus strain [ 12 , 13 ]. Mice subjected to a pentobarbital-induced sleep test on Day 14 showed significantly increased sleep time and decreased sleep latency after the administration of a specific L. fermentum strain for 14 days [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have shown the sleep-promoting effects of a single Lactobacillus strain [ 12 , 13 ]. Mice subjected to a pentobarbital-induced sleep test on Day 14 showed significantly increased sleep time and decreased sleep latency after the administration of a specific L. fermentum strain for 14 days [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the causal relationship between the altered composition of a particular bacterium and inadequate sleep is questionable; it is unclear whether the bacterium is a causal factor or inadequate sleep alters the bacterial composition as a sleep-inducing signal to compensate for inadequate sleep. A few studies have examined the effects of probiotic supplementation with a single species, such as Lactobacillus or Bifidobacterium , on the sleep states in animals [ 12 , 13 ] and humans [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also observed a higher abundance of the family Erysipelotrichaceae (phylum Firmicutes) in participants with poor sleep quality (no significant difference after correction), which is consistent with the previous results (Benedict et al 2016). However, the latest evidence provided by Lin et al (2021) indicated that Lactobacillus fermentum PS150 (PS150) could improve sleep conditions in the mice model and also induces gut microbiota remodeling, including an increased abundance of class Erysipelotrichia. Our findings do not confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep duration and quality may be essential targets for keeping healthy gut microbiota composition [ 16 ], and sleep disorders are also linked with changes in gut microbiota composition in animal and adult human models [ 83 ]. Lactobacilli and Bifidobacteria are beneficial bacteria in the gut [ 15 , 84 , 85 ], and Lactobacillus fermentum can improve sleep conditions in mice and effectively reduce sleep latency and the time to return to normal REM sleep [ 86 ]. Moreover, the combination of living Bifidobacterium and Lactobacillus mitigates anxiety- and depression-like behaviors in mice [ 87 ].…”
Section: Discussionmentioning
confidence: 99%